Floristic Study of Lichens from Satna and Panna Districts of Madhya Pradesh, India - Mohabe, S.; Mishra, G. K.; Upreti, D. K.; Trivedi, S. (Indian Forester, 2012)
The paper enumerates 50 species of lichens belonging to 25 genera and 14 families from Satna and Panna districts in Vindhyanchal Range of Madhya Pradesh. The Satna district is represented by the occurrence of 40 species of lichens belonging to 23 genera under 13 families. The districts showed occurrence of 21 corticolous and 18 saxicolous species, with dominance of crustose lichens represented by 25 species followed by 8 species of squamulose and 7 of foliose lichens. The Panna district showed occurrence of 37 species belonging to 21 genera under 12 families. Both saxicolous and corticolous lichens are represented by 18 species each while a single species is found both on rocks and bark of trees. The crustose lichens dominates the district with 21 species, followed by 8, 6 and 2 species of foliose, squamulose and leprose form respectively. The Mangifera indica trees in dense, moist shady mango orchard exhibit luxuriant growth of lichens under Physciaceae family. Among the saxicolous genera, the crustose and squamulose growth form of the member of lichen families Teloschistaceae and Peltulaceae exhibit their luxuriant growth in the area.